ON RELIGIOUS MORALITY AND UNIVERSAL RESPONSIBILITY AND DIALOGUE ACCORDING TO KUNG’S GLOBAL ETHICS (Religious dialogue and cooperation, 2025)
This paper explores the concept of universal responsibility and global ethics as essentialfoundations for achieving lasting peace in the modern interconnected world. It emphasizesthat genuine peace cannot be established through violence or coercion but through the cultivationof ethical values, moral awareness, and interreligious dialogue. The study argues that everyhuman action has both personal and universal dimensions, demanding responsibility not onlytoward oneself but also toward humanity, nature, and future generations. Within this framework,dialogue emerges as a fundamental ethical and communicative method for understanding, cooperation,and peaceful coexistence among individuals, nations, and religions. Drawing on theideas of thinkers such as Emil Brunner, the Dalai Lama, Emmanuel Levinas, and especially HansKüng, the paper highlights Küng’s project Global Ethics as a crucial attempt to establish a sharedmoral framework based on humanism and dialogue. The work underscores the necessity of interreligiousunderstanding and the development of a universal ethical paradigm grounded in justice,compassion, tolerance, and responsibility. The conclusion calls for an ethical revolution centeredon humanism and global solidarity, affirming that universal ethics should guide humanity towardbuilding a more humane, just, and harmonious world.
Keywords: universal responsibility; global ethics; dialogue; Hans Küng; peace